A Study on Importance of Digital Signature for E-Governance - Arpitha Martin; Sushanth Bhusal, (International Journal of Management Studies (IJMS), 2019)
The DigitalSignature is the method which is used to validate and authorize the content and users who are going to involve in the E-governance system. E-governance is the latest trend in many countries in which the government system is being online to deliver the governmentservices to the citizens. The services can be from Government to Citizen (G2C) and Government to Business (G2B) or Governmentto Government (G2G) or Government to Employee (G2E) or vice a versa. The vision of National e-Governance Plan (NeGP) of Government of India is to “make all Government services accessible to the common man in his locality, through Common Service Delivery Outlets and ensure efficiency, transparency and reliability of such services at affordable costs to realise the basic needs of the common man”. The key objective of this vision is to provide e-services - G2B and G2C - in a ubiquitous manner. People can access any application or any scheme fromanywhere, anytime. As it comes with the word online, the biggest concern is the security issue. To provide E-authentication to theuser there are many cryptographic techniques available. This paper discusses to increase the security, reliability, and non-repudiation of the user’s data or information using Digital signature. It is highly secured and well-known method to authenticate and verify an electronic transaction.